bahasa inggris Bahasa Inggris: Bahasa inggris - Mu'awanah, Elyatul; Ashfia, Ahmad; Huzaifi, Fikri (LP2M IAIN Sultan Amai Gorontalo, 2025)
Background: Arabic language education has undergone significant development from the classical period to the modern era, where various traditional methods and learning philosophies were applied to strengthen language understanding and Islamic values. However, in the era of globalization, innovative approaches are needed to address the needs of the current generation who tend to be more dynamic and familiar with digital technology. Aims: This research aims to analyze the historical traces of Arabic language education to identify effective learning elements in the past and evaluate their potential adaptation in modern learning design. Methods: This research used a literature study-based qualitative approach with a narrative systematic review type to find methods such as halaqah, muhadatsah (dialogue), and memorization-based approaches that remain relevant but require integration with modern technology, such as digital applications and online learning platforms. Results: The findings showed that combining historical elements with technological innovations can create learning methods, models, and media that not only retain the depth of language and cultural understanding but also attract younger generations. Thus, learning designs that combine traditional and innovative aspects are expected to increase the effectiveness of Arabic language learning in the era of globalization and expand its accessibility. Implications: The results of this study can serve as a reference for educational institutions and curriculum developers in designing Arabic learning approaches that are more adaptive and effective in the present.